Horizontal Stresses and Their Impact on Roof Stability at the Nelms No. 2 Mine - J. B. Lizak (International Conference on Ground Control in Mining, 1984)
This paper is not available for inclusion in the Proceedings at the time of printing, but it will be included as an insert.